E-government and Public Financial Management reform: An examination of SAKTI implementation - Gunawan Ari Nursanto; Seno Setyo Pujonggo; Muhammad Arief Hamdi; Virra Wirdhiningsih; Arief Febrianto (Universitas Nusa Cendana, 2026)
The digitalisation of public financial management in Indonesia has advanced through the Integrated Financial Management Information System (IFMIS), particularly the mandatory Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) for all central government work units. This article analyses SAKTI’s implementation at the Immigration Polytechnic, a strategic vocational institution under the Ministry of Law, expected to strengthen efficiency, transparency, and accountability in managing state funds. Using DeLone and McLean’s (2003) Information Systems Success Model, the study assesses system quality, information quality, service quality, use, user satisfaction, and net benefits. A case study design was employed, combining a survey of end-users with semi-structured interviews and document analysis. The findings show that SAKTI has improved standardisation and traceability of financial transactions, yet several socio-technical challenges persist, including unstable connectivity, system slowdowns during peak periods, limited user training, and varying levels of digital literacy. These constraints reduce user satisfaction and hinder the full realisation of organisational benefits. The study contributes to e-government and IFMIS literature in developing country bureaucracies and proposes practical recommendations to strengthen leadership commitment, capacity-building, and technical infrastructure to optimise SAKTI implementation in education-sector work units. Keywords: IFMIS; E-Government; Information Systems Success; Public Financial Management